Expression of suppressor of cytokine signaling genes in human elderly and Alzheimer's disease brains and human microglia. (27th August 2015) - Walker, D.G.; Whetzel, A.M.; Lue, L.-F.
Highlights: We identified SOCS-1 through SOCS-7 and CIS mRNA expression in human brains. We identified SOCS-1 through SOCS-7 protein expression in human brains. We showed increased expression of SOCS-2, SOCS-3 and CIS mRNA in AD brains. SOCS-2, SOCS-3 and CIS mRNA levels in brains correlated with plaque pathology. Amyloid beta increased SOCS-1, SOCS-2, SOCS-3 and CIS mRNA in human microglia. Abstract: Multiple cellular systems exist to prevent uncontrolled inflammation in brain tissues; the suppressor of cytokine signaling (SOCS) proteins have key roles in these processes. SOCS proteins are involved in restricting cellular signaling pathways by enhancing the degradation of activated receptors and removing the stimuli for continued activation. There are eight separate SOCS genes that code for proteins with similar structures and properties. All SOCS proteins can reduce signaling of activated transcription factors Janus kinase (JAK) and signal transducer and activator of transcription (STAT), but they also regulate many other signaling pathways. SOCS-1 and SOCS-3 have particular roles in regulating inflammatory processes. Chronic inflammation is a key feature of the pathology present in Alzheimer's disease (AD)-affected brains resulting from responses to amyloid plaques or neurofibrillary tangles, the pathological hallmarks of AD. The goal of this study was to examine SOCS gene expression in human non-demented (ND) and AD brains and in human brain-derived microglia to determine if AD-related pathology resulted in a deficit of these critical molecules. We demonstrated that SOCS-1, SOCS-2, SOCS-3 and cytokine-inducible SH2 containing protein (CIS) mRNA expression was increased in amyloid beta peptide (Aβ)- and inflammatory-stimulated microglia, while SOCS-6 mRNA expression was decreased by both types of treatments. Using human brain samples from the temporal cortex from ND and AD cases, SOCS-1 through SOCS-7 and CIS mRNA and SOCS-1 through SOCS-7 protein could be detected constitutively in ND and AD human brain samples. Although, the expression of key SOCS genes did not change to a large extent as a result of AD pathology, there were significantly increased levels of SOCS-2, SOCS-3 and CIS mRNA and increased protein levels of SOCS-4 and SOCS-7 in AD brains. In summary, there was no evidence of a deficit of these key inflammatory regulating proteins in aged or AD brains.